Effect of Problem Based Learning Models with the Help of Monopoly Game on the Mathematical Critical Thinking Abilities of Class IX Students of MTs Negeri 3 Majalengka - Suherman, Ade (Faculty of Tarbiya and Teacher Trainning, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
Abstract: This research was conducted based on the low critical mathematical thinking skills of class IX students at MTs Negeri 3 Majalengka. Researchers chose problem based learning models with the help of monopoly games to overcome students' mathematical abilities. The aim of this research was to find out how it was implemented and whether there was an influence of the problem based learning models with the help of the monopoly game on students' mathematical critical thinking abilities. The type of research used was quantitative research using experimental methods. The population of this study was all class IX, totaling 155 students, with a sample of 19 students in class IX A, and 21 students in class IX B. Data collection methods were carried out by observation and tests. Data analysis techniques used normality tests, homogeneity tests, and t tests. Based on the results of the t test againstpost-test obtained a value of 0.000 < 0.05, then H1 accepted. So it cauld be concluded that there was an influence between the modelsproblem based learning with the help of the monopoly game on mathematical critical thinking skills.